2015
DOI: 10.1371/journal.pone.0135567
|View full text |Cite|
|
Sign up to set email alerts
|

Viral Glycoprotein Complex Formation, Essential Function and Immunogenicity in the Guinea Pig Model for Cytomegalovirus

Abstract: Development of a cytomegalovirus (CMV) vaccine is a major public health priority due to the risk of congenital infection. A key component of a vaccine is thought to be an effective neutralizing antibody response against the viral glycoproteins necessary for cell entry. Species specificity of human CMV (HCMV) precludes direct studies in an animal model. The guinea pig is the only small animal model for congenital cytomegalovirus infection. Analysis of the guinea pig CMV (GPCMV) genome indicates that it potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
134
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(135 citation statements)
references
References 80 publications
(133 reference statements)
1
134
0
Order By: Relevance
“…The gH/gL complex has been identified as a potentially important target antigen, including in a congenital GPCMV infection model. In this study, a novel antibody therapy strategy was found to be effective in reducing the incidence of congenital CMV infection (36,58). Consequently, an effective immune response to both gB and gH/gL is likely an important factor for a successful vaccine against congenital CMV.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…The gH/gL complex has been identified as a potentially important target antigen, including in a congenital GPCMV infection model. In this study, a novel antibody therapy strategy was found to be effective in reducing the incidence of congenital CMV infection (36,58). Consequently, an effective immune response to both gB and gH/gL is likely an important factor for a successful vaccine against congenital CMV.…”
mentioning
confidence: 88%
“…Manipulation of an infectious GPCMV BAC has allowed the preliminary study of some viral genes (1,(30)(31)(32)(33)(34)(35)(36). Analysis of the viral genome (15,29) indicated that GPCMV encodes homologs to the HCMV glycoproteins (gB, gH, gL, gM, gN, and gO) in genes colinear with the HCMV genome (designated GP55, GP75, GP115, GP100, GP73, and GP74, respectively).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In human herpesvirus 6 (HHV-6) and HHV-7, the homologous protein also forms a complex with gH and gL (27,28), but to date no function has been assigned to this protein (29). Similarly to HCMV gO, murine and guinea pig cytomegalovirus (CMV) gO binds to gH/gL, and its deletion leads to a severely reduced cell-free infectivity (30,31), indicating that the function of gO is conserved among the various CMVs. An essential role of the gH/gL/gO complex for pathogenesis of murine CMV (MCMV) was recently demonstrated in a mouse model: a gO-deficient MCMV mutant was unable to establish infection in mice (32), indicating that gO plays a pivotal role for host-to-host transmission of CMV.…”
mentioning
confidence: 99%